Mutation G1629E increases von Willebrand Factor cleavage via a cooperative destabilization mechanism - Aponte-Santamaria, Camilo; Gräter, Frauke (Biophysical journal, 2017)
The large multimeric glycoprotein von Willebrand Factor (VWF) plays a pivotal adhesive role during primary hemostasis. VWF is cleaved by the protease ADAMTS13 as a down-regulatory mechanism to prevent excessive VWF-mediated platelet aggregation. For each VWF monomer, the ADAMTS13 cleavage site is located deeply buried inside the VWF A2 domain. External forces in vivo or denaturants in vitro trigger the unfolding of this domain, thereby leaving the cleavage site solvent-exposed and ready for cleavage. Mutations in the VWF A2 domain, facilitating the cleavage process, cause a distinct form of von Willebrand disease (VWD), VWD type 2A. In particular, the VWD type 2A Gly1629Glu mutation drastically accelerates the proteolytic cleavage activity, even in the absence of forces or denaturants. However, the effect of this mutation has not yet been quantified, in terms of kinetics or thermodynamics, nor has the underlying molecular mechanism been revealed. In this study, we addressed these questions by using fluorescence correlation spectroscopy, molecular dynamics simulations, and free energy calculations. The measured enzyme kinetics revealed a 20-fold increase in the cleavage rate for the Gly1629Glu mutant compared with the wild-type VWF. Cleavage was found cooperative with a cooperativity coefficient n = 2.3, suggesting that the mutant VWF gives access to multiple cleavage sites of the VWF multimer at the same time. According to our simulations and free energy calculations, the Gly1629Glu mutation causes structural perturbation in the A2 domain and thereby destabilizes the domain by ∼10 kJ/mol, promoting its unfolding. Taken together, the enhanced proteolytic activity of Gly1629Glu can be readily explained by an increased availability of the ADAMTS13 cleavage site through A2-domain-fold thermodynamic destabilization. Our study puts forward the Gly1629Glu mutant as a very efficient enzyme substrate for ADAMTS13 activity assays.